Ex vivo transtympanic permeation of the liposome encapsulated S. pneumoniae endolysin MSlys - Silva, Maria Daniela (2022)
An increase in bacterial resistance to systemic antibiotics has sparked interest into alternative antimicrobial compounds as well as methods for effective local, non-invasive drug delivery. Topical treatments, however, may be hindered by the presence of biological barriers, such as the tympanic membrane in the case of otitis media. Herein, the transtympanic permeation ability of liposomes loaded with the pneumococcal endolysin MSlys and of free MSlys was evaluated ex vivo. MSlys loaded in PEGylated liposomes showed an increased permeation across human tympanic membranes, as compared to its free form, being able to reduce the pneumococcal cell load after 2 h of permeation. However, antipneumococcal activity was no longer detected after 4 h of permeation and hydrolysis of the endolysin was observed after an extended incubation time ( 48 h). This work provides a first assessment of a successful, non-invasive delivery method for endolysins across an intact tympanic membrane. Findings have implications for non-systemic, local treatment of otitis media.